(untitled) (CIPEEX, 2022)
THIS PAPER PROPOSES TO PRESENT THE EXPERIENCE REPORT OF THE UNICIDAD ITINERANTE - APAEANO LOVE DAY PROJECT CONDUCTED BY THE UNIVERSITY OF ANÁPOLIS - UNIEVANGŠLICA, IN PARTNERSHIP WITH THE ASSOCIATION OF PARENTS AND FRIENDS OF THE EXCEPTIONAL OF ANÁPOLIS (APAE). OBJECTIVE: TO GUIDE THE PUBLIC ABOUT THE TYPES OF INITIAL LESIONS CHARACTERISTIC OF ORAL CANCER, TOGETHER WITH THE PREVENTION EXAM. METHODS: A BRIEF EXPLANATION OF THE CHARACTERISTICS OF NEOPLASTIC LESIONS WAS MADE THROUGH THE PERSONNEL INTERESTED IN PARTICIPATING IN THE INTRA ORAL EVALUATION, AFTER WHICH THE ORAL EVALUATION WAS CARRIED OUT BY THE STUDENTS ENROLLED IN THIS SOCIAL ACTION. IF THERE WERE ANY CASES OF SUSPICION OF ORAL CANCER, THE PATIENT WOULD BE REFERRED TO THE DISCIPLINE OF DIAGNOSIS OF THE COURSE OF DENTISTRY. RESULTS: 13 PEOPLE WERE EVALUATED RECEIVING GUIDANCE AND PREVENTION CARE ABOUT THE IMPORTANCE OF ORAL CANCER.&NBSP; PALAVRAS-CHAVE (OU KEYWORDS, OU PALABRAS CLAVE): ORAL NEOPLASMS, DENTISTRY, ORAL EXAMINATION, DIAGNOSIS.